Translation, cultural adaptation, and psychometric validation of the Simplified Chinese Athlete Sleep Behavior Questionnaire (ASBQ-CN) in Chinese athletes - Leo Guohui Lin; Zora Yuyang Zhang; Jeremy Rui Chang; Matthew W. Driller; Jiebin Huang; Tony Kwok Wing Lee; Siu-Ngor Fu; Arnold Yu Lok Wong (PLoS ONE, 2026)
Objective To translate, adapt, and validate the Simplified Chinese Athlete Sleep Behavior Questionnaire (ASBQ-CN) for both adolescent and adult athletes. Design Cross-sectional psychometric evaluation. Methods A total of 480 Chinese athletes (19.9 ± 4.4 years) and 408 non-athletes (23.3 ± 3.9 years, for discriminant validity evaluation) were recruited. Psychometric testing included internal consistency, test–retest reliability, content validity, exploratory and confirmatory factor analyses, and convergent and discriminant validity. For robust factor analysis of ordinal data, parallel analysis with polychoric correlations and ordinary least squares estimations were choose. Results The ASBQ-CN demonstrated acceptable internal consistency (Cronbach’s α total of 0.76) and test–retest reliability (intraclass correlation coefficient of 0.78). The standard error of measurement and minimal detectable change were 3.13 and 8.67, respectively. Content validity achieving indices of 1.0 at toth item- and scale-level. Factor analyses supported a four-factor structure with acceptable model fit indices (comparative fit index = 0.95, Tucker Lewis index = 0.94, root mean square error of approximation = 0.06, and standardized root mean square residual = 0.09). Convergent validity was confirmed by moderate correlations with the Pittsburgh Sleep Quality Index (r total = 0.44) and Sleep Hygiene Index (r total = 0.50). Although total ASBQ-CN scores did not significantly differ between athletes and non-athletes, significant item-level differences were identified (p < 0.0028). Furthermore, athletes with poor sleep hygiene showed significant higher ASBQ-CN score (p < 0.001). Conclusion The ASBQ-CN is a valid and reliable instrument for evaluating sleep behavior in both adolescent and adult Chinese athletes, which could inform personalized interventions.